Development of "Core Syllabus" for Facial Anatomy Teaching to Aesthetic Physicians: A Delphi Consensus. Issue 3 (March 2018) - Kumar, Narendra; Swift, Arthur; Rahman, Eqram
Abstract : Background: A detailed understanding of facial anatomy, specifically the vascular framework, is crucial for delivering safe nonsurgical aesthetic procedures. To date, there is no core document based on consensus for the teaching of facial anatomy to aesthetic physicians exists. The aim of this study was to ascertain the most critical anatomical structures for avoiding disastrous complications during nonsurgical aesthetic procedures. Methods: After a detailed literature review, Delphi questionnaire was developed listing 154 anatomical structures of the face and neck for consensus review. Thirty-five international experts in surgical and nonsurgical facial aesthetics were invited to complete an online survey designed to rank the relevance of each anatomical element on a Likert scale from 1 (not at all important) to 4 (very important) or 5 (no opinion). Consensus for items included in the core syllabus was predefined as achieving a Cronbach's α ≥ 0.90 and an agreement score of ≥ 80%. Results: Thirty-four international experts (97.14%) completed the iterative online Delphi survey. The consensus among the specialists polled was achieved after 1 round of the survey (Cronbach's α = 0.94). The expert panel reached an agreement score of ≥ 80% on 137 of the 154 anatomical structures listed. Conclusion: The outcome of this Delphi study represents an essential first step in systematizing an evidence-based facial anatomy "Core Syllabus" for the teaching of aesthetic physicians and practitioners. This "Core Syllabus" will act as a blueprint for the educators while crafting a program.